2017
DOI: 10.22159/ajpcr.2017.v10i2.15514
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanoparticles for the Oral Delivery of Low Molecular Weight Heparin: In Vitro and in Vivo Assessment

Abstract: Objective: The objective of the present study was to prepare and evaluate a novel oral formulation of nanoparticles for the systemic delivery of lowmolecular-weight heparin (LMWH).Methods: Nanoparticles were prepared by polyelectrolyte complexation method using polymers, i.e., sodium alginate and chitosan (CH). Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), X-ray diffraction (XRD), entrapment efficiency, In vitro release and scanning electron microscopic studies were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The viscosity of alginate/HPMC mixtures affected the diameters and densities of beads and the volumes of entrapped drug substance. Alginate-chitosan beads increased in diameter with increasing chitosan concentrations, reflecting the formation of polyelectrolyte complexes between carboxyl groups of alginate and amine groups of chitosan [31][32][33][34]. Previous studies have shown that bead sizes are normally distributed over 50-2000 µm [35].…”
Section: Discussionmentioning
confidence: 95%
“…The viscosity of alginate/HPMC mixtures affected the diameters and densities of beads and the volumes of entrapped drug substance. Alginate-chitosan beads increased in diameter with increasing chitosan concentrations, reflecting the formation of polyelectrolyte complexes between carboxyl groups of alginate and amine groups of chitosan [31][32][33][34]. Previous studies have shown that bead sizes are normally distributed over 50-2000 µm [35].…”
Section: Discussionmentioning
confidence: 95%
“…Nanoparticles are usually <100 nm in size. They consist of different biodegradable materials such as natural or synthetic polymers, lipids, or metals [2]. Gold nanoparticles (AuNPs) have been widely developed as a multifunctional platform for various biomedical applications [3] such as biosensing systems, cancer therapies, drug delivery, and pharmaceuticals [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles have several advantages, such as improvement in the intracellular infiltration, circulation time of the drug, and enhanced hydrophobic solubility [1]. They consist of different biodegradable materials such as natural or synthetic polymers, lipids, or metals [2]. Gold nanoparticles (AuNPs) are some of the most widely employed nanoparticles in medicine.…”
Section: Introductionmentioning
confidence: 99%